Creation of shared value in cooperatives: informal institutions’ perspective of small-sized banana growers from Colombia - Maestre Matos, Marcela (2023)
Purpose: This study aims to identify informal institutions for bottom-of-the-pyramid (BoP) business models in the agricultural sector through the case study of banana growers’ cooperatives. Design/methodology/approach: A case study of six banana cooperatives from Colombia was conducted. The research followed a mixed design, using both qualitative and quantitative data and the application of structural equations. Findings: This study shows that social capital, networking and alliances are essential in BoP businesses. Originality/value: Authors defined a model of informal institutional factors for the generation of economic and social value in inclusive business, using the new institutional theory and the conceptual development of BoP in agri-business.